Marketing Strategy Product Financing of PT. Bank Sumut KCP Syari’ah Simpang Kayu Besar - Rahma, Aini; Lubis, Irsad (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
Each Islamic bank has a variety of products offered to suit the wishes of the people. In offering its products, there is competition between Islamic banks and conventional banks, resulting in the need for a strategy in the sales of each bank. Sales are often identified with a world full of sweet promises but it is not necessarily proven whether the product is in accordance with what has been promised. This is what must be proven in good Islamic sales management in the sale of goods or services, that Islamic marketing is not a world full of deception. Because Islamic marketing is the highest level in sales, namely marketing spirituality, where ethics, values and norms are highly respected. Research results show that marketing strategy product financing in this bank focus on education public about superiority product financing sharia- based, increasing personal relationship with Customer through customer relationship management (CRM) approach. In analyzing research data using qualitative descriptive methods, only describing the results of the questions interview with management of Bank Sumut KCP Syariah Simpang Kayu Besar, observation direct, and study document related.. This research is motivated by the growth of Islamic banks that positively share participation in economic stability, but in practice there are criticisms. Likewise, scholars and religious scholars have different opinions regarding the role and position of Islamic banks, some of them think that Islamic banks are similar to conventional banks. The results of the research prove that the implementation of financing product sales at PT. Bank Sumut Kcp Syari'ah Simpang Kayu Besar.